Rapid bactericidal activity of an amphiphilic polyacrylate terpolymer system comprised of same-centered comonomers with 2-carbon and 6-carbon spacer arms and an uncharged repeat unit. Issue 17 (6th February 2017) - Punia, Kamia; Punia, Ashish; Chatterjee, Kaushiki; Mukherjee, Sumit; Fata, Jimmie; Banerjee, Probal; Raja, Krishnaswami; Yang, Nan-Loh
Abstract : Cationic amphiphilic polyacrylate terpolymers with rapid bactericidal activity against E. coli and S. aureus . Abstract : The global health threat of antimicrobial resistance has created a pressing need to develop practical alternatives to conventional antibiotic agents. Peptide mimetic synthetic amphiphilic polymers are known to non-specifically disrupt the bacterial cell surface thus leading to highly hindered bacterial resistance development. We investigated the antibacterial activities of a terpolymer macromolecular architecture with a combination of 6-carbon and 2-carbon spacer arms (distance from polymer backbone to pendent cationic center) interspersed with counits with hydrophobic side groups. A random copolymer with a combination of 6-carbon spacer arm repeat units (60 mol%) and 2-carbon spacer arm (40 mol%) units is moderately active against bacteria and shows very low hemolytic activity. Incorporation of comonomer units with alkyl side groups, by replacing different levels of 2-carbon spacer arm counit, led to substantial increments in antibacterial activities without detrimental effects on hemolytic activities leading to highly selective (bacteria over red blood cells) antibacterial activity. Time-kill studies revealed rapid bactericidal activity of the terpolymer against both Staphylococcus aureus and Escherichia coli with 100% killing efficiency achieved within 1 h of polymer treatment, corresponding to a 5-log reduction of bacterial colony forming units. These results indicate the high potential of this amphiphilic terpolymer architecture in the development of alternatives to antibiotics.